Development of Multisensory Media in Islamic Religious Education at SLBN 1 Parepare - Mulya Hamdani; Sitti Jamilah Amin; St. Aminah R; Firman; Musyarif (DIDAKTIKA, 2025)
This study discusses the development of multisensory learning media in the subject of Islamic Religious Education (PAI) at SLBN 1 Parepare. This media is designed to assist students with special needs in understanding the material of Taharah, including the conditions of wudu, the pillars of wudu, and things that invalidate wudu, by engaging multiple senses through interactive visual and audio elements. The aim of this research is to analyse the development process of the multisensory media and evaluate its validity, practicality, and effectiveness in improving students' learning outcomes. The research method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study included 10 students and one PAI teacher at SLBN 1 Parepare. Data collection techniques involved observation, interviews, tests, and documentation, and the data were analysed using quantitative analysis. The results of the study indicate that the developed multisensory media meets the criteria of validity, practicality, and effectiveness, with significant improvements in students' learning outcomes and positive responses from both students and teachers. Therefore, this media can serve as an innovative alternative in PAI learning at Special Needs Schools (SLB).